(untitled) (Archeomatica, 2024)
The acquisition technologies developed by Haltadefinizione allow you to obtain very high resolution digital images of the paintings. Thanks to specially designed algorithms, in fact, it is possible to combine a large quantity of individual photographic shots of small portions of the portraits to obtain what is called a gigapixel image.